Carboxylated acrylonitrile butadiene-natural rubber latex blends with methyl methacrylate grafted natural rubber latex: Mechanical properties and morphology - Lim, H.M; Tan, K.S (Journal of Rubber Research, 25(5): 413-419., 2022)
Commercially available carboxylated acrylonitrile butadiene latex (XNBR) was physically blended with natural rubber latex (NR) at varying blend ratios to investigate its effect on the mechanical properties and morphology. Methyl methacrylate grafted natural rubber latex (MG) was added to the latex blends as a third polymer to study whether it could enhance the mechanical properties of the latex blend films. It was found that the tensile strength of the blend films irrespective of composition decreased when the two latexes were blended as compared to the virgin latex films. The modulus 300 decreased while the elongation at break and tear strength of the blend films increased gradually as the ratio of NR increased in the blend films. It was found that the MG did not enhance the mechanical properties of the XNBR/NR blend films under the current experimental condition. AFM phase imaging analysis revealed enhanced polymer distribution and evidence of NR-MG-XNBR interactions.
Keywords: Carboxylated acrylonitrile butadiene latex; Natural rubber latex; Blend; Methyl methacrylate grafted natural rubber latex; Phase imaging